PENGARUH BRAND IMAGE, BRAND TRUST DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE ORIGINOTE DI KOTA BATAM - Jenny Jenny; Suhardi Suhardi (SCIENTIA JOURNAL, 2026)
This study examines the influence of brand image, brand trust, and product quality on purchasing decisions of The Originote skincare products in Batam City. The increasing competition in the skincare industry and fluctuations in The Originote’s market ranking indicate the importance of understanding key factors that drive consumer purchasing decisions. The objective of this research is to analyze both partial and simultaneous effects of brand image, brand trust, and product quality on purchasing decisions. This study employs a quantitative explanatory approach. Data were collected through questionnaires distributed to 119 respondents who had purchased and used The Originote products, selected using purposive sampling. The data were analyzed using multiple linear regression, supported by t-tests and F-tests. The results reveal that brand image, brand trust, and product quality each have a positive and significant effect on purchasing decisions. Simultaneously, all three variables significantly influence consumers’ purchasing decisions. These findings indicate that a strong brand image, high consumer trust, and superior product quality play an essential role in encouraging consumers to purchase The Originote products. This research is expected to provide practical insights for companies in developing effective marketing strategies to enhance competitiveness in the skincare industry. Keywords : Brand Image; Brand Trust; Product Quality; Purchase Decision